Perbedaan Hasil Belajar Siswa Sistem Reguler dengan Sistem Boarding School pada Mata Pelajaran IPS: (Studi Pada SMP Negeri 2 Gunung Meriah dan SMP Darul Muta`allimin) - Fitri Handayani; Hendri Fauza; Nuriza Dora (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The aim of this research is to determine the differences in social studies learning outcomes between regular and boarding school students. This research uses a quantitative approach with comparative methods. Data collection techniques use tests and documentation. The data analysis technique uses the t test. From the results of calculations that have been carried out using the t test with a significance level of 5%, the calculated value of tcount ≤ ttable or 1.462 ≤ 2.005746 is obtained. So Ha is rejected and H0 is accepted. It can be concluded from the results of these calculations that there is no significant difference in social studies learning outcomes between regular schools and boarding schools. This is proven by the R2 obtained which was only 2.9% while the remaining 97.1% was influenced by other variables.